Respon Tanaman Selada (Lactuca sativa L.) Terhadap Pemberian Pupuk Organik Urine Kambing - Hitimala, Budianto; Rehatta, Herman; Nendissa, Jeanne I (Pattimura University Ambon Maluku Indonesia, 2023)
This study aims to determine the response of lettuce plants to the application of goat urine organic fertilizer. The study was a Complete Randomized Design with 1 factor 4 repeats. The results showed that the concentration of goat urine organic fertilizer showed that K4 treatment (200 mL concentration) on the parameters of plant height (cm), number of leaves (strands), leaf area (cm2), fresh weight of plants (g), fresh weight of roots (g), and harvest index gave the highest yield on lettuce plants followed by other treatments such as K5 (Concentration 250 mL), K6 (Concentration 300 mL), K7 (Concentration 350 mL), K3 (Concentration 150 mL), K2 (Concentration 100 mL), K1 (Concentration 50 mL) and the lowest of the parameters above corresponds to K0 (without control). The concentration of organic fertilizer from goat urine significantly influences the K4 treatment. This shows that this concentration can provide the nutrients needed to support optimal vegetative growth of lettuce plants.